The Display Behavior of Sub-Adult Greater Bird-of-Paradise (Paradisaea apoda): A Learning Process from an Adult? - Pramunandya, Raka Aditya; Mardiastuti, Ani; Mulyani, Yeni; Chandra, Vinoba (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The Greater Bird-of-Paradise (Paradisaea apoda) is a bird that performs a courtship display (lekking) to attract females during the mating season. The objective of this study was to examine the display behavior of adult and sub-adult males on lek trees as a learning process by a sub-adult and identify the lek trees. The research was conducted in the Tunas Timber Lestari Ltd. Production Forest in central mainland Papua, in a non-breeding season. After a lek tree was found, a video recording was conducted. Analysis was performed from the video. The lek tree was an emergent species with a dense canopy. An adult male was observed to perform a dance display in front of sub-adult males, even in the absence of females. When adult males performed display, the sub-adult were observed the adult males in an upside-down position. The sub-adult also danced, but not as complete as the adult, suggesting that there was a learning process by the sub-adult. This study revealed that the sub-adult/young males of the bird-of-paradise has the ability to dance inherit from their fathers, and then perfect the dance through practice and watching adults. The lek tree surely need to be protected for the survival for this species.